AN OVERVIEW OF THE CONCEPT OF LEAN CONSTRUCTION AND THE BARRIERS IN ITS IMPLEMENTATION - R, Radhika; Sukumar, S. (International Journal of Engineering Technologies and Management Research, 2017)
Many project management approaches have emerged to improve performance in the construction industry. Lean construction is one of the ways to design systems to minimize wastage of materials, time and effort in order to generate maximum possible amount of value. Lean Six Sigma is the combination of two well-known techniques Lean and Six sigma which focuses on quality improvement, reduction in variation and waste elimination. The purpose of this paper is to make an overview of the lean concept and also to include the barriers in implementing this approach. A detailed review of the literature has been done with the view of collecting relevant data necessary for the paper. A questionnaire survey has been conducted to find the barriers affecting its implementation. It was found that six main barriers are there in implementing the concept of Lean construction. These data were subjected to statistical analysis and necessary preventive measures are recommended for mitigating those barriers that were identified. By the implementation of Lean, it is found that, there is a significant reduction in waste, cost and time.